Myanmar Agricultural Performance Survey Round Four: Note on Sample Characteristics and Weighting - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2024)
The Myanmar Agricultural Performance Survey (MAPS) is a nationally and sub-nationally representative phone survey with the objective of collecting bi-annual data on agricultural indicators including crop production and sales, input use, crop marketing, farm and livestock assets, and farm services. The Myanmar Household Welfare Survey (MHWS)is a nationally and sub‐nationally representative phone survey with the objective of collecting quarterly data on household and individual welfare indicators, including poverty, food security, dietary quality, subjective wellbeing, and coping strategies. MAPS is a sub-sample survey that includes farming households from MHWS. There are four Rounds of MAPS. MAPS Rounds 1 and 3 were conducted between January and March 2022 and 2023 and collect recall data on monsoon production. MAPS Round 2 and 4 were conducted between June and September 2022 and 2023 and collect recall data on dry season production (pre/post monsoon season). MAPS Round 4 consists of 11 modules (A-K) that are each included in the clean dataset and unique by household ID (hhid). Modules A, B, and J are introductory and closing modules that only include information on the call and confirmation of demographic information connected to MHWS. The remaining modules provide data on farmer demographics and agricultural production and marketing. Module C consists of background and demographic information. This includes data on farmer demographics along with farm area and crops grown. Module D provides data on rice production and sales for pre/post monsoon 2022 and 2023, including rice variety, amounts produced and sold, and farmgate prices. Module E contains similar information to Module D but pertaining to pulses and oilseeds. Module F consists of data on farm input use including purchased inputs, mechanization, labor, and the effect of natural shocks. Module G presents information on crop marketing and Module H provides data on farm and livestock assets. Module I contains data on farm services including agricultural extension, credit, mobility issues in the community, travel times to access services, contract farming, crop residues, and changes in rice consumption and paddy growing practices. Module K contains information on change in rice consumption and paddy growing practices.